O perímetro irrigado de Morada Nova como laboratório de um modelo de desenvolvimento rural no Semiárido Nordestino: o projeto-piloto da política de irrigação e desenvolvimento agrícola da SUDENE/DNOCS - Silva, Francisco Antonio da (2023)
The Jaguaribe river basin, located in the state of Ceará, was chosen in the 1960s as a representative region of the Polígono das Secas for the realization of studies and the elaboration and execution of hydro-agricultural valorization projects, constituting itself in a laboratory of experimentation of policies for the reorganization of the agrarian structure and agricultural development, with the implementation of public irrigation projects. This research focuses on the issue of rural development, more precisely within the scope of agrarian and agricultural policies formulated and implemented by the Brazilian State in the Northeast region, from the 1960s onwards, and the relationships that these policies establish with the process of change or agrarian transformation, that is, the role played by agrarian policies and agricultural policies in the reorganization of the land structure and agricultural production in the northeastern semi-arid region. The research focuses on a particular aspect of agrarian change, embodied in the issue of public irrigation projects, the empirical locus of which is the Irrigated Perimeter of Morada Nova, located in the municipalities of Morada Nova and Limoeiro do Norte, in the Banabuiú river valley, a tributary of the Jaguaribe River, chosen at the end of the 1960s as an experimental laboratory for a model of rural development in the northeastern semi-arid region, with the objective of creating family farming centers as the basis for future companies of family crops transformed for the production of food and industrial crops, which would supply the domestic market and provide raw material for regional industries. From the study of this "laboratory" of rural development, we analyzed the formulation and execution of agrarian and agricultural policies that aspire to the disorganization of the local agricultural production system from the expropriation and displacement of rural communities that had the land and agricultural production as the main conditions for carrying out the processes of social reproduction. I use extensive documentation to analyze and understand the agrarian changes that occurred in this region of the interior of the state of Ceará caused by the implementation of the Irrigated Perimeter of Morada Nova. The research comes to the conclusion that the installation of this public irrigation project entailed immense human and environmental sacrifices in the region, with the forced displacement of 18,000 people and the destruction of the local agricultural production system, constituting the first experience of joint work between SUDENE and DNOCS with large irrigation projects and serving as a model for the future actions of these two federal authorities.